Student’s creative model in solving mathematics controversial problems - Subanji Subanji; Toto Nusantara; Sukoriyanto Sukoriyanto; Satriya Adika Arif Atmaja (Jurnal Cakrawala Pendidikan, 2023)
For students to compete with the rapid advancement in science, technology, and the arts, creativity must be more than just a necessary skill. This study of levels of creativity performed when addressing statistical issues is a follow-up to earlier studies. To create a distinctive model, a controversial aspect was used. The study revealed that there were five levels of creative models, in addition to the three levels of the earlier research: pre-imitation, imitation, modification, combination, and construction. The pre-imitation stage is defined by the subject's limited capacity for imitation. The level of imitation is determined by the act of copying methods even when one does not actually understand them. The modification level is essentially defined by the process of altering a procedure so that it can be applied to solve an issue. The process for merging several settings or problem-solving strategies also serves to define the level of combination. The construction level is determined by the process of developing new methods to handle problems.